Comparative Hypertestosteronemic Effects of the Erythropoietin and the U-74389G - Tsompos, Constantinos; Panoulis, Constantinos; Triantafyllou, Aggeliki; Zografos, Constantinos; Zografos, George C.; Papalois, Apostolos (Free Radicals and Antioxidants)
Background: This study is to find out in which direction two antioxidant promising molecules, the erythropoietin and the U-74389G, affect serum Testosterone (T) levels and what the magnitude of this alteration is. The posttreatment effects on serum Testosterone (T) levels were calculated, separately by each drug and afterwards a comparative calculation was following. Objectives: The estimation was extracted by the results of the 2 previous studies, each of which had estimated a certain influence, after the respective drug administration in an induced Ischemia-Reperfusion (IR) rat experiment. Materials and Methods: The 2 temporal experimental endpoints at which the serum T levels were measured were the 60th reperfusion min (for the 3 groups A, C and E) as well the 120th reperfusion min (for the other 3 groups B, D and F). Especially, the groups A and B were the placebo ones, the groups C and D were the post Epo; whereas the groups E and F were the post L administration. Results: The first previous study of Epo presented a non-significant hypertestosteronemic effect by 0.276%±0.272% (p-value=0.3006). Similarly, the second previous study of U-74389G presented also a non-significant hypertestosteronemic effect by 0.111%±0.179% (p-value=0.5245). The results of these 2 studies co-calculated as belonging to the same experimental setting, provided the outcome of L being just by 0.4046004 [0.4035126 - 0.4056911] less hypertestoteronemic than Epo (p-value=0.0000). Conclusion: The intrinsic antioxidant capacity of U-74389G ascribes just 0.4046004 [0.4035126 - 0.4056911] less hypertestoteronemic influence than Epo (p-value=0.0000).
Keywords: Ischemia; Erythropoietin; U-74389G; Serum testosteronelevels; Reperfusion; Comparative hypertestosteronemia